Analysis of human-machine interface of a multi-modal handheld device - Moudgalya Akshara Vishwanath (2017)
With the inclusion of robots on the industry floor, workers are forced to be more aware of their movement while working so they can avoid collisions, make small repairs when needed and improve functionality. Till date, the control over industrial robots is done using a regular computer system - monitor, keyboard and mouse or a facsimile of one like a touchpad for stationary robots. This doesn't allow workers much flexibility and freedom of movement. To allow workers freer movement and the ability to use a single device to control multiple robots, a multi-modal handheld device was designed. To provide the user with real time instructions and feedback, the device is also connected to augmented reality goggles. The objective of this project is to test the usability of the system consisting of ARgoggles, the handheld device and a robot intended for industrial use. The user wears the goggles and uses the handheld device to remotely control the robot's movements. Using a test pool of Mechanical engineers who are representative of the final users, a user evaluation was conducted, followed by semi-structured interviews. Before the actual usability test, a pilot test with 3 users was conducted where they performed the task and gave feedback through interviews. The test began with a demo, followed by having the users complete a navigation task. Once the usability test was done, the users were given an online questionnaire to fill and the system was evaluated. The number of participants for the test is 20. The results of the study varied depending on the method of data collection due to the amount of response time each respondent was given per method. As a majority, the respondents were hesitant to shift to a new method of control that has a lot of information input. However, 35% were open to the design, provided they had enough training and time was given to gain expertise. The statistics obtained from the tests conducted showed such a trend among users and it can be shown that increased familiarity increases comfort. The report includes the evaluation forms created, transcripts of interviews and a summary of the potential areas for improvement and recommendations for the same.